Synthesis and Modification of Hydroxyapatite Nanofiber for Poly(Lactic Acid) Composites with Enhanced Mechanical Strength and Bioactivity - Han-Seung Ko; Sangwoon Lee; Jae Young Jho (Nanomaterials, 2021)
To enhance the bioactivity of poly(lactic acid) (PLA), a potential bone repair material, without the lowering of mechanical strength, hydroxyapatite (HA) was introduced in the form of nanofibers as the filler for application in spinal implant materials. HA nanofibers (HANF) with aspect ratio as high as ~100 were synthesized by controlling the starting pH of the reaction. While the tensile and flexural strength of PLA/HANF composites were enhanced compared with those of PLA resin, and were higher for the composites with HANF of higher aspect ratio. To further strengthen the composites, HANF was grafted with PLA chain to form HANF-g-PLA, which could improve the interface between the HANF and matrix PLA. PLA/HANF-g-PLA composites showed even higher tensile and flexural strength than PLA/HANF composites, apparently due to the better dispersion and interfacial adhesion. The composite containing 10 wt% HANF-g-PLA showed the flexural strength of 124 MPa, which was 25% higher than that of PLA resin. In the bioactivity test using a simulated body fluid solution, the rate and uniformity of the apatite growth were observed to be higher for the composites with HANF, and were even higher for those with HANF-g-PLA. This study suggested the possibility of using the PLA/HANF-g-PLA composite in the field of spinal implant materials.